Dispute resolution of offences committed by juveniles under Omani law - Alyazidi, Badar Khamis Said; Negasi, Mohamed Ibrahim; Abubakar, Yusuf Sani; Laeba, Muhammad (Hassiba Benbouali University of Chlef, 2021)
Although Omani law contains provisions on amicable settlement of disputes, it has clearly neglected offences committed by juveniles. There is only one law that applies to both adults and juveniles. Nevertheless, the latter should be given more attention and care to spare juveniles from the complexity of trials that may have a bad impact on them. The present research aims to achieve a number of objectives which include defining the concept of juveniles and juvenile law under Omani justice system, presenting a dispute resolution systemunder the Omani judicial system which relates to juveniles for both criminal and civil offences and suggesting ways to improve its function. The research is based on a set of research methodologies. The research adopts an inductive approach by extrapolating legal articles concerning the settlement of disputes under the Omani legal system. Moreover, the research also adopts an analytical approach to analyze the general principles and rules of Omani law in the settlement of disputes related to juveniles. Finally, a comparative approach is taken whenrequired. A comparison is made with Islamic law. The study concludes that there are legislative shortcomings of Omani laws in the settlement of disputes of offences committed by juveniles. The shortcomings need to be resolved byenacting laws that require amicable settlements in juvenile cases by a judge compelling a victim to settle amicably before resorting to a court. In addition to this, a special body should be established which is concerned with the amicable settlement of disputes involving juveniles